Pemphigus Vulgaris Presented with Cheilitis - Zaheer Abbas; Zahra Safaie Naraghi; Elham Behrangi (Case Reports in Dermatological Medicine)
Background. Pemphigus vulgaris is an autoimmune blistering disease affecting the mucous membrane and skin. In 50 to 70% of cases, the initial manifestations of pemphigus vulgaris are oral lesions which may be followed by skin lesions. But it is unusual for the disease to present with initial and solitary persistent lower lip lesions without progression to any other location. Main Observations. We report a 41-year-old woman with dry crusted lesions only on the lower lip, clinically resembling actinic cheilitis and erosive lichen planus, but histopathological evaluation showed unexpected results of suprabasal acantholysis and cleft compatible with pemphigus vulgaris. We treated her with intralesional triamcinolone 10 mg/mL for 2 sessions and 2 g cellcept daily. Patient showed excellent response and lesions resolved completely within 2 months. In one-year follow-up, there was no evidence of relapse or any additional lesion on the other sites. Conclusion. Cheilitis may be the initial and sole manifestation of pemphigus vulgaris. Localized and solitary lesions of pemphigus vulgaris can be treated and controlled without systemic corticosteroids.